2022
DOI: 10.3390/bios12060363
|View full text |Cite
|
Sign up to set email alerts
|

A Soft and Skin-Interfaced Smart Patch Based on Fiber Optics for Cardiorespiratory Monitoring

Abstract: Wearables are valuable solutions for monitoring a variety of physiological parameters. Their application in cardiorespiratory monitoring may significantly impact global health problems and the economic burden related to cardiovascular and respiratory diseases. Here, we describe a soft biosensor capable of monitoring heart (HR) and respiratory (RR) rates simultaneously. We show that a skin-interfaced biosensor based on fiber optics (i.e., the smart patch) is capable of estimating HR and RR by detecting local ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…It must be considered that the perturbations caused by the heart beating are smaller than, and thus partially hidden by, the ones caused by the overlapping respiratory activity. Although this significant difference between the contribution of breathingrelated and heart-related movement on the FBGs output, we have already demonstrated the possibility to perform a simultaneous monitoring of these two activities using FBGbased approach [20]. Moreover, the microscopic vibrations induced on the chest surface by the mechanical activity of the heart can be stressed in the absence of the respiratory contribution (for instance, working in the apnoea phase).…”
Section: A Wearable System Working Principlementioning
confidence: 96%
“…It must be considered that the perturbations caused by the heart beating are smaller than, and thus partially hidden by, the ones caused by the overlapping respiratory activity. Although this significant difference between the contribution of breathingrelated and heart-related movement on the FBGs output, we have already demonstrated the possibility to perform a simultaneous monitoring of these two activities using FBGbased approach [20]. Moreover, the microscopic vibrations induced on the chest surface by the mechanical activity of the heart can be stressed in the absence of the respiratory contribution (for instance, working in the apnoea phase).…”
Section: A Wearable System Working Principlementioning
confidence: 96%
“…The dummy sensor was multiplexed to the flexible sensor for enabling the T monitoring and compensating the values induced by thermal effects. In fact, literature studies showed that the thermal sensitivity of an FBG encapsulated within a Dragon-skin silicone matrix is comparable to the one of an unencapsulated sensor [ 7 , 8 ]; hence the values experienced by the dummy sensor may be subtracted to the ones of the dumbbell-shaped sensor to perform the T compensation. To better analyze the thermal influence, reference values of T were measured by using a commercial system (BME280 by BOSCH) with a sampling rate of 10 Hz.…”
Section: Plant Wearables For Growth Monitoring: Test Data Analysis An...mentioning
confidence: 99%
“…These characteristics can be found in the flexible sensors recently proposed for developing new wearable devices for humans. Distinctive features of these systems include high softness for better compliance with the human body, lightweight, unobtrusive design, and improved user conformability [ 5 , 6 , 7 , 8 , 9 ]. Although these wearable systems are already impacting healthcare by enabling the continuous and real-time monitoring of human health, their use in agricultural settings is still significantly left behind [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, FBG-based innovative systems can be encapsulated within silicone rubbers allowing a design close-fitting to the specific application and ensuring high flexibility and robustness [ 32 , 33 , 34 ]. As evidenced by scientific studies, the encapsulation of FBGs within silicone materials can impact the metrological characteristics of the entire developed system (e.g., in terms of sensitivity) since they are affected by the mechanical properties (e.g., Young’s modulus) of the selected material, the assigned geometry, and the interface bond between the sensor and the rubber coating [ 32 , 35 , 36 ]. Therefore, developing such smart devices requires an ad hoc design based on carefully selecting the silicone rubber, shape, and dimensions, which should be well-tailored to the specific application.…”
Section: Introductionmentioning
confidence: 99%